2023
DOI: 10.1002/advs.202205563
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Gut Microbiota and Its Metabolites in Tumorigenesis or Development of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the most common cancer of the digestive system with high mortality and morbidity rates. Gut microbiota is found in the intestines, especially the colorectum, and has structured crosstalk interactions with the host that affect several physiological processes. The gut microbiota include CRC‐promoting bacterial species, such as Fusobacterium nucleatum, Escherichia coli, and Bacteroides fragilis, and CRC‐protecting bacterial species, such as Clostridium butyricum, Streptococcus thermophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 245 publications
(303 reference statements)
0
8
0
Order By: Relevance
“…These incongruent trends can be explained since it has been observed that the association of Christensenellaceae with CRC depends on the type of specific mutation present [ 66 , 67 ]. On the other hand, as shown in Table 3 , we observed a significant decrease in the abundance of the family Enterobacteriaceae in the luteolin cohort, which may be related to an unhealthy state (due to the presence of lipopolysaccharide in this family, as well as other virulence factors), since this family is associated with CRC due to the production of the organic compound trimethylamine n-oxide [ 68 ]. Other families, such as Eggerthellaceae and Anaerovoracaceae, showed a reduction in the luteolin cohort, while the Clostridia vadinBB60 group and Butyricicoccaceae experienced an increase.…”
Section: Discussionmentioning
confidence: 99%
“…These incongruent trends can be explained since it has been observed that the association of Christensenellaceae with CRC depends on the type of specific mutation present [ 66 , 67 ]. On the other hand, as shown in Table 3 , we observed a significant decrease in the abundance of the family Enterobacteriaceae in the luteolin cohort, which may be related to an unhealthy state (due to the presence of lipopolysaccharide in this family, as well as other virulence factors), since this family is associated with CRC due to the production of the organic compound trimethylamine n-oxide [ 68 ]. Other families, such as Eggerthellaceae and Anaerovoracaceae, showed a reduction in the luteolin cohort, while the Clostridia vadinBB60 group and Butyricicoccaceae experienced an increase.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity of intestinal flora varies with the origin and evolution of CRC[ 67 ]. Simultaneously, increased abundance of pro-tumor bacteria such as polyketide synthase-positive (pks+) Escherichia coli ( E. coli ), enterotoxigenic Bacteroides fragilis, and Fusobacterium nucleatum can promote intestinal inflammation via toxins or metabolites, facilitate tumor cell proliferation and migration, and create an immunosuppressive microenvironment that limits anti-tumor immunity[ 68 , 69 ]. The preceding data indicate that the intestinal flora plays an important role in the development of CRC and influences tumor chemotherapy and immunotherapy[ 70 ].…”
Section: Potential Carcinogenic Effect Of H Pylori ...mentioning
confidence: 99%
“…The gut microbiota communicates with the host immune system through pattern recognition receptor signaling, inflammasome, and cytokines. 17 As a natural functional component, dietary fiber is usually divided into two categories: insoluble dietary fiber (IDF) and soluble dietary fiber (SDF); among them, SDF has significant antitumor activity and can have a prebiotic effect by increasing beneficial bacteria and improving intestinal environment. 18 Zhu et al found that sweet potato pomace SDF can be thoroughly decomposed by microorganisms distributed in the human digestive tract, regulating the structure of the human intestinal bacterial community, which has a significant effect on prevention and treatment of colon cancer and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have found that some specific bacteria, such as Fusobacterium nuclei, Escherichia coli, and Bacteroides fragilis, are associated with multiple occurrence mechanisms of colorectal cancer. The gut microbiota communicates with the host immune system through pattern recognition receptor signaling, inflammasome, and cytokines . As a natural functional component, dietary fiber is usually divided into two categories: insoluble dietary fiber (IDF) and soluble dietary fiber (SDF); among them, SDF has significant antitumor activity and can have a prebiotic effect by increasing beneficial bacteria and improving intestinal environment .…”
Section: Introductionmentioning
confidence: 99%